2017
DOI: 10.1038/ja.2017.102
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive drug combinations and their potential to combat antibiotic resistance

Abstract: Antibiotic effectiveness often changes when two or more such drugs are administered simultaneously, and unearthing antibiotic combinations with enhanced efficacy (synergy) has been a longstanding clinical goal. However, antibiotic resistance, which undermines individual drugs, threatens such combined treatments. Remarkably, it has emerged that antibiotic combinations whose combined effect is lower than that of at least one of the individual drugs can slow or even reverse the evolution of resistance. We synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 105 publications
(189 reference statements)
0
58
1
1
Order By: Relevance
“…That the FoR for HC2184 was the same as the FoR for HC2149 and HC2169 is interesting as the cross-resistance profiles and results of DiaMOND analysis suggested that these compounds interact differently with MmpL3. While the antagonistic interactions identified by DiaMOND suggest that scaffold combinations may lower the activity of a single inhibitor, antagonistic drug combinations have been proposed to decrease the rate of resistance 42, 43 . It therefore may be possible to design a single inhibitor that fuses more than one scaffold to decrease the rate of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…That the FoR for HC2184 was the same as the FoR for HC2149 and HC2169 is interesting as the cross-resistance profiles and results of DiaMOND analysis suggested that these compounds interact differently with MmpL3. While the antagonistic interactions identified by DiaMOND suggest that scaffold combinations may lower the activity of a single inhibitor, antagonistic drug combinations have been proposed to decrease the rate of resistance 42, 43 . It therefore may be possible to design a single inhibitor that fuses more than one scaffold to decrease the rate of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the antibiotic disc assay (Table 1), 'on agar' antibiotic resistance was confirmed by growing cultures in TSB (without antibiotics) and plating the cultures on TSA alone, and on TSA containing the chosen antibiotics ( Figure 3). This was done to determine if there was any antagonism that might be at play when multiple antibiotics are added in combination [34][35][36][37]. Based on the antibiotic disc assay (Table 1), 'on agar' antibiotic resistance was confirmed by growing cultures in TSB (without antibiotics) and plating the cultures on TSA alone, and on TSA containing the chosen antibiotics ( Figure 3).…”
Section: Determination Of Salmonella Antibiotic Resistance (Disc Assay)mentioning
confidence: 99%
“…In the United States alone, an estimated 2.8 million antibiotic-resistant infections occur every year ( 1 ). Many previously treatable infections, such as tuberculosis ( 2 ), urinary tract infections ( 3 ), and even Staphylococcus -mediated skin infections ( 4 ) now require higher doses of more powerful antibiotics, and the development of novel antimicrobials is limited ( 5 , 6 ). One potential alternative treatment strategy is the use of drug combinations, which have been used successfully in HIV treatment ( 7 , 8 ) and cancer chemotherapy ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%